Fascist Europe : From Italian Supremacy to Subservience to the Reich (1932-1943) - Fioravanzo, Monica (Berghahn Books, 2024)
By shedding light on an often-overlooked aspect of Fascism and Nazism, this book examines the ambitious plans for a new European order conceived by Italian intellectuals, historians, geographers, politicians, and even student representative of the Fascist University Groups (GUF). Through expert reconstruction of the debate on this envisaged order's development, Monica Fioravanzo opens a window into the theoretical arena that shaped relationships between German, Italy and the other Axis nations and provides insight into how the project was anticipated to unite the Fascist regime in Italy and the Nazi Reich.